The sinister omen - Keene, Carolyn; Frame, Paul 1913- (New York Wanderer Books, 1982)
While on vacation in Fort Lauderdale, Nancy and her friends help a wealthy woman plagued with burglars who don't steal anything.
Keywords: Mystery and detective stories